The South Asian Association for Regional Cooperation (SAARC) : an emerging collaboration architecture - Saez, Lawrence, 1965- (Milton Park, Abingdon, Oxon ; New York : Routledge, 2011)
"This work aims to examine the institutional structure, objectives, and effectiveness of the SAARC in its role as South Asia's leading regional institution"--
Includes bibliographical references and index.
Keywords: South Asian Association for Regional Cooperation; South Asian cooperation; Interregionalism -- South Asia; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / International Relations / Treaties; South Asia -- Foreign relations